2007
DOI: 10.1042/bj20070234
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian GPI-anchored proteins require p24 proteins for their efficient transport from the ER to the plasma membrane

Abstract: The GPI (glycosylphosphatidylinositol) moiety is attached to newly synthesized proteins in the lumen of the ER (endoplasmic reticulum). The modified proteins are then directed to the PM (plasma membrane). Less well understood is how nascent mammalian GPI-anchored proteins are targeted from the ER to the PM. In the present study, we investigated mechanisms underlying membrane trafficking of the GPI-anchored proteins, focusing on the early secretory pathway. We first established a cell line that stably expresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 25 publications
11
76
0
Order By: Relevance
“…While our work was in progress, Takida et al reported that a knockdown of p23 results in delayed plasma membrane appearance of a transfected VSV-G-GPI hybrid molecule and of transfected decay-accelerating factor, a GPI-anchored protein (Takida et al, 2008). This work is consistent with our data.…”
Section: Role Of P24 Proteins In Selective Er Export Of Gpianchored Psupporting
confidence: 83%
“…While our work was in progress, Takida et al reported that a knockdown of p23 results in delayed plasma membrane appearance of a transfected VSV-G-GPI hybrid molecule and of transfected decay-accelerating factor, a GPI-anchored protein (Takida et al, 2008). This work is consistent with our data.…”
Section: Role Of P24 Proteins In Selective Er Export Of Gpianchored Psupporting
confidence: 83%
“…Because of this abnormal glycan structure, we speculate that PIG-O defi cient cells might have a defect in sorting of free or protein anchored GPIs into ER exit sites. The ER exit of GPI-anchored proteins is controlled by glycan remodeling and p24 complexes act as cargo receptors for GPI anchor sorting into COPII vesicles ( 6,39,49 ). In agreement with this model, we observed a global increase in HexCer levels in the remodeling mutants PGAP1 and PGAP5 as well as for the p24 family proteins.…”
Section: Cholesterol Ester Levels Are Reduced In Cells That Do Not Sysupporting
confidence: 76%
“…In contrast to the observed changes in HexCer and ceramide, total sphingomyelin levels were not affected in the proteins associate with p24 family proteins ( 6,39 ). We therefore analyzed the lipid profi le of cells in which the GPI remodeling enzymes PGAP1, PGAP5, or the p24 family members p23 or p24 were silenced respectively.…”
Section: Very Long Chain Sphingomyelin Levels Are Partially Affected mentioning
confidence: 99%
“…7C). p24 cycles between the ER and Golgi, is a major component of both COPII and COPI vesicles (50), serves as a primer for COPI vesicle formation (51,64), and, in isoform-specific fashion, appears to serve as a cargo receptor for glycosylphosphatidylinositol-anchored proteins (65,66), G-protein coupled receptors (67), and the Wnt ligand wingless (68,69). Proper p24 trafficking and interaction with other binding partners requires hetero-oligomerization among several closely related p24 family isoforms (70 -72).…”
Section: Alg-2/sec31a-prr Interactions Acutely Regulate Cargo Receptomentioning
confidence: 99%